1981
DOI: 10.1172/jci110310
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Labeling and Clearance of Lung Surfactant Phospholipids in Rabbit

Abstract: A B S T R A C T Turnover and clearance of lung surfactant phospholipids were studied with particular reference to myoinositol-induced perturbation in the acidic phospholipids. Administration of myoinositol decreased [3H]palmitate and [32P]phosphate incorporation into phosphatidylglycerol by 80-90% in whole lung, and by 94-99% in lamellar bodies and in alveolar lavage. The increased incorporation of radioactive isotopes into phosphatidylinositol following myoinositol, was inverse to the decrease in phosphatidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Hallman et al (20) reported that radiolabeled natural surfactant was cleared from the airways and alveoli of adult rabbits to lung tissue, and the labeled phospholipids became in part associated with lamellar bodies. These observations suggested that alveolar surfactant might be recycled back into type I1 cells for reprocessing and resecretion.…”
Section: Resultsmentioning
confidence: 99%
“…Hallman et al (20) reported that radiolabeled natural surfactant was cleared from the airways and alveoli of adult rabbits to lung tissue, and the labeled phospholipids became in part associated with lamellar bodies. These observations suggested that alveolar surfactant might be recycled back into type I1 cells for reprocessing and resecretion.…”
Section: Resultsmentioning
confidence: 99%
“…Uptake of surfactant phospholipids by alveolar cells was demonstrated for endotracheally administered tracer amounts of surfactant (4,(28)(29)(30)(31) and recently for treatment doses of surfactant (8,32). Bartussio et al (33) demonstrated in 3-d-old rabbits that SP-C is taken up by the lung tissue similarly to phospholipids (33).…”
Section: Discussionmentioning
confidence: 98%
“…This mixture was supplemented with 3 H-DPPC (specific activity 87 µCi/mg) to a final radioactivity of 1.46 nCi/µg lipid. After evaporation of the chloroform, 1 ml 0.2 M phosphate buffered saline (PBS, pH 7.4) was added and the mixture was incubated at 50°C for 15 minutes.…”
Section: Liposome Preparationmentioning
confidence: 99%
“…For resecretion experiments liposomes were prepared as described above with the following composition: 5.4 mg DPPC, 1 mg PG, 2.5 mg egg yolk PC, 1 mg cholesterol, and 0.1 mg cholesterol oleate in chloroform. 15 This mixture was supplemented with 3 H-DPPC (specific activity 87 µCi/mg) to a final radioactivity of 1.46 nCi/µg lipid and with 14 C-cholesterol oleate (specific activity 115 mCi/mg) to a final radioactivity of 1 nCi/µg lipid. The mixture was stored at 4°C and used within 1 week.…”
Section: Liposome Preparationmentioning
confidence: 99%
See 1 more Smart Citation